mtDNA phylogeny and evolution of laboratory mouse strains - Goios, Ana (Cold Spring Harbor Laboratory Press, 2007)
Inbred mouse strains have been maintained for more than 100 years, and they are thought to be a mixture of four different mouse subspecies. Although genealogies have been established, female inbred mouse phylogenies remain unexplored. By a phylogenetic analysis of newly generated complete mitochondrial DNA sequence data in 16 strains, we show here that all common inbred strains descend from the same Mus musculus domesticus female wild ancestor, and suggest that they present a different mitochondrial evolutionary process than their wild relatives with a faster accumulation of replacement substitutions. Our data complement forthcoming results on resequencing of a group of priority strains, and they follow recent efforts of the Mouse Phenome Project to collect and make publicly available information on various strains.